Preparation method and application of co-doped modified Ti4O7 electrode and electrode

Through the preparation method of co-doped modified Ti4O7 electrode, the stability and cost problems existing in the long-term use of the existing chlorine-eliminated electrode are solved, and the efficient, stable and inexpensive chlorine-eliminated properties are achieved. It is suitable for a variety of water treatment applications .

CN119456046AActive Publication Date: 2025-02-18DONGGUAN UNIV OF TECH +2

Patent Information

Application Number
CN202410433775.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-02-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

The existing chlorine-eliminated electrodes have problems such as dissolution of active substances, mechanical corrosion, and chemical dissolution during long-term use. The precious metal resources are limited and the cost is high, making it difficult to meet the needs of high efficiency, stability and inexpensiveness.

Method used

Using the preparation method of co-doped modified Ti4O7 electrode, the modified chlorine with improved chlorine is produced by mixing Ti4O7 powder with metal and non-metal source, adding binder and organic dispersant after ball milling, heating and stirring with ultrasonic, drying and sintering. Performance electrodes.

Benefits of technology

It significantly improves the chlorine evolution reaction activity and selectivity of Ti4O7 electrode, enhances the stability and mechanical properties of the electrode, reduces costs, and is suitable for the treatment of wastewater containing ammonia nitrogen pollutants and disinfection and sterilization of small water bodies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the field of electrochemical oxidation, and particularly discloses a preparation method of a co-doped modified Ti4O7 electrode, and the preparation method comprises the following steps: 1, mixing Ti4O7 powder, a metal source and a non-metal source, and carrying out ball milling to obtain mixed powder; and 2, adding a binder and an organic dispersant into the mixed powder, and carrying out ultrasonic treatment, heating and stirring, drying and sintering to obtain the co-doped modified Ti4O7 electrode. The co-doped modified Ti4O7 electrode prepared by the invention has excellent chlorine evolution and sterilization performance, and can be applied to purification treatment of wastewater containing ammonia nitrogen pollutants and long-acting maintenance of disinfection and sterilization of small water bodies such as circulating water, landscape water, ballast water and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical oxidation, and more specifically, to a preparation method and application of a co-doped modified Ti4O7 electrode and an electrode. Background Art

[0002] The electrochemical chlorine evolution reaction can utilize Cl in the solution - It is converted into active chlorine, and chlorine gas is prepared and hydrolyzed to produce hypochlorous acid. This process not only has excellent treatment effect on ammonia nitrogen wastewater, but also the ability to generate active chlorine in situ also gives it excellent bactericidal and disinfecting effect, showing broad application prospects. The key core of electrochemical chlorine evolution performance lies in the chlorine evolution electrode, which determines the working energy efficiency of the entire unit. At present, the commonly used chlorine evolution electrodes on the market are traditional ruthenium iridium-shaped stable electrodes, but in long-term applications, technical problems that need to be solved are gradually exposed, such as long-term use of active substances. Dissolution, mechanical corrosion of violent bubbles, formation of insulating oxides of the plate substrate, and chemical dissolution caused by chlorine generation or pickling, etc., greatly test the stability and service life of the electrode. At the same time, limited precious metal resource reserves and high application costs have prompted us to find and develop a more efficient, stable and cheap new sustainable chlorine evolution electrode.

[0003] Titanium Suboxide (Ti n O 2n-1 ) is a new type of environmentally friendly ceramic membrane electrode material with great research and application value, and Ti4O7 is the material with the best conductivity. It also has the advantages of high chemical stability, high corrosion resistance, high oxygen evolution potential, etc., showing good chlorine evolution selectivity and high chlorine evolution activity potential, and is expected to be used stably for a long time in the harsh environment of chlorine evolution, especially its cost price is much lower than the ruthenium iridium shape stable electrode on the market. For a single Ti4O7 electrode, its chlorine evolution performance still has a lot of room for improvement. Summary of the invention

[0004] In order to improve the chlorine evolution performance of Ti4O7 electrode, the present application provides a preparation method and application of a co-doped modified Ti4O7 electrode and an electrode.

[0005] In the first aspect, the present application provides a method for preparing a co-doped modified Ti4O7 electrode, using the following technical solution:

[0006] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0007] Step 1: Mix Ti4O7 powder, metal source and non-metal source, and ball mill to obtain mixed powder;

[0008] Step 2: Add a binder and an organic dispersant to the mixed powder, perform ultrasonic treatment, heat and stir, dry, and sinter to obtain a co-doped modified Ti4O7 electrode.

[0009] Preferably, the amount of the metal source is 1-3wt% of the Ti4O7 powder, and the amount of the non-metal source is 5-9wt% of the Ti4O7 powder.

[0010] Preferably, the metal source is one or more of ruthenium chloride, cobalt chloride or cobalt nitrate, cerium chloride, europium chloride or europium acetate, tin chloride and antimony chloride, and the non-metal source is one or more of boric acid, phosphoric acid, sodium fluoride and sodium sulfide.

[0011] By adopting the above technical scheme, the doping metal source can reduce the electron density of the Ti center in the Ti4O7 electrode, which is conducive to the nucleophilic reagent Cl - The proximity of the electrode is beneficial to improving the chlorine evolution reaction activity of the electrode, and at the same time can also improve the stability of the Ti4O7 electrode; and doping with non-metallic sources can effectively increase the number of unsaturated oxygen sites in the Ti4O7 electrode, which is beneficial to the efficient adsorption and conversion of chlorine evolution intermediate active substances on the electrode, greatly improving the chlorine evolution selectivity of the electrode.

[0012] Preferably, the particle size of the Ti4O7 powder is 20 to 45 μm.

[0013] By adopting the above technical solution, the appropriate particle size helps the Ti4O7 powders to be in close contact with each other, which can ensure the density of the final product and thus ensure the stability of the electrode.

[0014] Preferably, the amount of the binder is 5-7wt% of the Ti4O7 powder.

[0015] Preferably, the binder is nitrogen-containing heterocyclic zinc-based metal organic framework nanoparticles.

[0016] By adopting the above technical scheme, nitrogen-containing heterocyclic zinc-based metal organic framework nanoparticles have a large specific surface area and porosity. After adding them into the system, they can effectively adsorb and bond the various raw material components to improve the stability of the electrode; at the same time, after high-temperature sintering, the nitrogen-containing heterocyclic zinc-based metal organic framework nanoparticles can be transformed into metal organic framework-derived nitrogen-doped carbon, which can significantly improve the electron transfer efficiency of the electrode. In addition, the unsaturated oxygen atoms bound to the carbon defect sites will also become important adsorption active sites for chlorine intermediates in the chlorine evolution process, effectively improving the chlorine evolution function of the electrode.

[0017] Preferably, the organic dispersant is selected from one or more of isopropanol, ethanol and acetone.

[0018] Preferably, it also includes flake graphene and spherical graphene, the amount of flake graphene is 2-3wt% of the Ti4O7 powder, and the amount of spherical graphene is 3-5wt% of the Ti4O7 powder; the mesh number of flake graphene is 1500-2000 mesh, and the mesh number of spherical graphene is 4000-5000 mesh.

[0019] By adopting the above technical solution and compounding flaky graphene and spherical graphene, the raw materials can be effectively contacted and densely stacked in the system. After sintering, the number of reactive active sites on the electrode surface can be increased, thereby further improving the performance of the electrode.

[0020] Preferably, the ball milling process is: the rotation speed is 1100-1400 r / min, and the time is 20-30 min;

[0021] The ultrasonic time is 30-50min, the heating and stirring temperature is 50-70°C, the stirring speed is 200-300r / min, the drying temperature is 70-90°C, and the drying time is 15-24h;

[0022] The sintering process is as follows: sintering heating rate of 40-70°C / min, sintering temperature of 1100-1200°C, sintering time of 15-30min, and high pressure condition of 2-4MPa.

[0023] By adopting the above technical solution and selecting a suitable sintering process, the quality of the finished product can be effectively ensured.

[0024] In the second aspect, the present application provides a co-doped modified Ti4O7 electrode, which adopts the following technical solution:

[0025] A co-doped modified Ti4O7 electrode is prepared by a preparation method.

[0026] In a third aspect, the present application provides an application of a co-doped modified Ti4O7 electrode, using the following technical solution:

[0027] The invention discloses an application of a co-doped modified Ti4O7 electrode for water treatment.

[0028] In summary, this application has the following beneficial effects:

[0029] 1. The present application distorts the Ti4O7 lattice by doping with metal sources, adjusts the state of unsaturated oxygen atoms by doping with non-metal sources, and utilizes the synergistic regulation of the electronic structure of the Ti4O7 electrode by binary, ternary or multi-metal co-doping, so that the chlorine evolution reaction activity and selectivity of the electrode are significantly enhanced.

[0030] 2. The present application uses metal organic framework nanoparticles as a binder to prepare Ti4O7 electrodes, so that the Ti4O7 electrodes have higher electron transfer efficiency. At the same time, the electrodes formed by high-temperature sintering and pressing have good mechanical stability, and Ti4O7 itself has excellent acid and alkali resistance, which are conducive to the long-term repeated and stable use of the electrodes in harsh chlorine evolution environments.

[0031] 3. Compared with the commercial shape-stable electrodes commonly used in the chlor-alkali industry, the co-doped modified Ti4O7 electrode prepared in this application has better comprehensive chlorine evolution performance and great cost advantages. It can be flexibly used in the efficient and harmless treatment of wastewater containing ammonia nitrogen pollutants and the long-term disinfection and sterilization of small water bodies such as landscape water, circulating water, and ballast water. It has a very broad prospect for market promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 is a low-magnification scanning electron microscope image of the electrode in Example 1;

[0033] Figure 2 is a high-magnification scanning electron microscope image of the electrode prepared in Example 1;

[0034] Figure 3 1 is the linear sweep voltammetric curve of the electrodes prepared in Examples 1-3 and Comparative Example 1;

[0035] Figure 4 are electrochemical impedance spectra of the electrodes prepared in Examples 1-3 and Comparative Example 1;

[0036] Figure 5 It is a comparison chart of the Faraday efficiency of the electrodes prepared in Examples 1-3 and Comparative Examples 1-4. DETAILED DESCRIPTION

[0037] The present application is further clarified and described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The nitrogen heterocyclic zinc-based metal organic framework nanoparticles used in this application were prepared with reference to Example 1 in the patent publication 201811036011X.

[0039] Example 1

[0040] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0041] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.02 g of ruthenium chloride and 0.1 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0042] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0043] Example 2

[0044] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0045] 2 g of Ti4O7 powder with a diameter of 35 μm, 0.04 g of europium chloride and 0.14 g of sodium fluoride were mixed and ball-milled at a speed of 1300 r / min for 30 min to obtain a mixed powder;

[0046] Add 0.12g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml acetone to the mixed powder, ultrasonicate for 50min, heat at 70℃, stir at 300r / min until almost dry, and then dry at 80℃ for 20h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 60℃ / min, a sintering temperature of 1200℃, a sintering time of 15min, and a high pressure condition of 3MPa to obtain a co-doped modified Ti4O7 electrode.

[0047] Example 3

[0048] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0049] 2 g of Ti4O7 powder with a diameter of 45 μm, 0.06 g of tin chloride and 0.18 g of phosphoric acid were mixed and ball-milled at a speed of 1400 r / min for 30 min to obtain a mixed powder;

[0050] Add 0.14g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml ethanol to the mixed powder, ultrasonicate for 40min, heat at 60℃, stir at 200r / min until almost dry, and then dry at 90℃ for 18h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 70℃ / min, a sintering temperature of 1200℃, a sintering time of 20min, and a high pressure condition of 4MPa to obtain a co-doped modified Ti4O7 electrode.

[0051] Example 4

[0052] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0053] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.04 g of ruthenium chloride and 0.1 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0054] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0055] Example 5

[0056] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0057] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.06 g of ruthenium chloride and 0.1 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0058] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0059] Example 6

[0060] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0061] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.02 g of ruthenium chloride and 0.14 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0062] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0063] Example 7

[0064] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0065] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.02 g of ruthenium chloride and 0.18 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0066] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0067] Example 8

[0068] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0069] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.02 g of ruthenium chloride, 0.04 g of 1500 mesh flake graphene, 0.06 g of 4000 mesh spherical graphene and 0.1 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0070] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0071] Example 9

[0072] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0073] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.02 g of ruthenium chloride, 0.06 g of 2000-mesh flake graphene, 0.1 g of 5000-mesh spherical graphene and 0.1 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0074] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0075] Example 10

[0076] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0077] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.02 g of ruthenium chloride, 0.1 g of 1500 mesh flake graphene and 0.1 g of boric acid were mixed and ball milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0078] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0079] Embodiment 11

[0080] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0081] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.02 g of ruthenium chloride, 0.1 g of 4000 mesh spherical graphene and 0.1 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0082] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0083] Example 12

[0084] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0085] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.1 g of ruthenium chloride and 0.1 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0086] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0087] Embodiment 13

[0088] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0089] 2 g of Ti4O7 powder with a diameter of 20 μm, 0.02 g of ruthenium chloride and 0.04 g of boric acid were mixed and ball-milled at a speed of 1100 r / min for 20 min to obtain a mixed powder;

[0090] Add 0.1g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml isopropanol to the mixed powder, ultrasonicate for 30min, heat at 50℃, stir at 200r / min until almost dry, and then dry at 70℃ for 24h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 40℃ / min, a sintering temperature of 1100℃, a sintering time of 30min, and a high pressure condition of 2MPa to obtain a co-doped modified Ti4O7 electrode.

[0091] Comparative Example 1

[0092] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0093] 2 g of Ti4O7 powder with a diameter of 20 μm and 0.06 g of ruthenium chloride were mixed and ball-milled at a speed of 1400 r / min for 30 min to obtain a mixed powder;

[0094] Add 0.14g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml acetone to the mixed powder, ultrasonicate for 40min, heat at 60℃, stir at 200r / min until almost dry, and then dry at 90℃ for 18h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 70℃ / min, a sintering temperature of 1100℃, a sintering time of 20min, and a high pressure condition of 4MPa to obtain a co-doped modified Ti4O7 electrode.

[0095] Comparative Example 2

[0096] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0097] 2 g of Ti4O7 powder with a diameter of 20 μm and 0.14 g of boric acid were mixed and ball-milled at a speed of 1300 r / min for 30 min to obtain a mixed powder;

[0098] Add 0.12g nitrogen heterocyclic zinc-based metal organic framework nanoparticles and 30ml acetone to the mixed powder, ultrasonicate for 50min, heat at 70℃, stir at 300r / min until almost dry, and then dry at 80℃ for 20h under vacuum conditions; finally, use spark plasma sintering to sinter at high temperature and high pressure, with a sintering heating rate of 50℃ / min, a sintering temperature of 1200℃, a sintering time of 15min, and a high pressure condition of 3MPa to obtain a co-doped modified Ti4O7 electrode.

[0099] Comparative Example 3

[0100] A method for preparing a co-doped modified Ti4O7 electrode comprises the following steps:

[0101] 2 g of Ti4O7 powder with a diameter of 35 μm, 0.04 g of cobalt chloride and 0.14 g of sodium sulfide were mixed and ball-milled at a speed of 1300 r / min for 30 min to obtain a mixed powder;

[0102] The sintering was carried out by spark plasma sintering under high temperature and high pressure, with a sintering heating rate of 60°C / min, a sintering temperature of 1100°C, a sintering time of 20min, and a high pressure condition of 4MPa. After completion, a co-doped modified Ti4O7 electrode was obtained.

[0103] Comparative Example 4

[0104] A commercially available ruthenium-iridium electrode was used as a comparative example, with a diameter of 20 mm.

[0105] Performance Testing

[0106] 1. Morphology analysis

[0107] The electrode structure in Example 1 was observed using a scanning electron microscope. Figure 1 As shown in Figure 2, the Ti4O7 electrode is sintered in good condition, and the electrode has a micron-scale porous structure. Figure 2 As shown, nitrogen-heterocyclic zinc-based metal organic framework nanoparticles are distributed between the particles in the Ti4O7 electrode, indicating that the nitrogen-heterocyclic zinc-based metal organic framework nanoparticles have an excellent bonding effect and can effectively improve the conductivity of the electrode.

[0108] 2. Chlorine evolution performance test

[0109] The electrodes prepared in Examples 1-3 and Comparative Example 1 were respectively used as electrodes to be tested, the Ag / AgCl electrode was used as a reference electrode, and the platinum electrode was used as a counter electrode, and the performances were respectively tested and recorded;

[0110] Take a sample and measure the polarization curve of the working electrode by linear voltammetry. The electrolyte is 0.3M NaCL solution, the scanning rate is 20mV / s, and the voltage range is 0-1.6V to evaluate the chlorine evolution activity of the electrode. Figure 3 As shown, compared with Comparative Example 1, the electrodes prepared in Examples 1-3 exhibited better chlorine evolution performance; the chlorine evolution current increased rapidly, at 10 mA / cm 2 Under the current density condition, the overpotential of the electrode in Examples 1-3 is significantly lower than that in Comparative Example 1, indicating that the co-doping modification of the Ti4O7 electrode using a metal source and a non-metal source in the present application can effectively reduce the overpotential of the chlorine evolution reaction of the Ti4O7 electrode and enhance the chlorine evolution activity.

[0111] Take the sample for electrochemical impedance spectroscopy test, the results are as follows Figure 4 As shown, the AC impedance of the electrodes in Examples 1-3 is significantly smaller than that of the electrodes in Comparative Example 1, indicating that the electrodes in Examples 1-3 have higher electron transfer efficiency and faster reaction kinetics in the chlorine evolution reaction.

[0112] The samples were taken and the Faraday efficiency was tested by iodine titration to evaluate the chlorine evolution selectivity of the electrode. The electrolyte was 0.3M NaCL solution and the current density was 30mA / cm 2 , the results are as follows Figure 5 As shown, the electrodes in Examples 1-3 exhibit better chlorine evolution selectivity, less oxygen evolution side reaction, and high current utilization.

[0113] 3. Ammonia nitrogen oxidation degradation performance test

[0114] The sample was used as the anode and the pure Ti4O7 electrode was used as the cathode. The simulated ammonia nitrogen wastewater was subjected to electro-oxidation treatment. The initial ammonia nitrogen concentration was 100 mg / L and the current density was 30 mA / cm 2 , chloride ion concentration 2000mg / L, detection of 90min ammonia nitrogen removal rate, the results are shown in Table 1.

[0115] Table 1 Ammonia nitrogen oxidation degradation performance test results

[0116]

[0117]

[0118] Referring to Table 1, compared with Comparative Examples 1-4, the electrodes in Examples 1-3 have better removal effects on ammonia nitrogen, indicating that co-doping the metal source and the non-metal source to modify the Ti4O7 electrode can effectively improve the chlorine evolution performance of the electrode.

[0119] In combination with Example 1, Example 4-Example 7, Example 12 and Example 13, by limiting the amount of metal source and non-metal source, it can be effectively ensured that the electrode has a better chlorine evolution effect; in combination with Example 1, Example 8-Example 11, the compounding of flaky graphene and spherical graphene can improve the performance of the electrode to a certain extent.

[0120] 4. Sterilization performance test

[0121] The sample was used as the anode and the pure Ti4O7 electrode was used as the cathode. 100 mL of ... 7 CFU / mL) was used to test the bactericidal and disinfecting performance. After 3 minutes of reaction, the contents of Staphylococcus aureus and Escherichia coli in the solution were detected. The results are shown in Table 2.

[0122] Table 2 Sterilization performance test results

[0123]

[0124]

[0125] Referring to Table 2, it can be seen that compared with comparative examples 1-4, the electrodes in Examples 1-3 have better sterilization effects, indicating that the electrodes prepared according to the preparation method in this application have excellent chlorine evolution sterilization efficacy.

[0126] In addition, the present invention also provides a modified Ti4O7 electrode prepared by the preparation of the above-mentioned co-doped modified Ti4O7 electrode and the application of the prepared modified Ti4O7 electrode in water body treatment. Specifically, the electrode has high efficient chlorine evolution reaction activity and selectivity, and can be widely used in the purification of wastewater containing ammonia nitrogen pollutants and the long-term maintenance of disinfection and sterilization of small water bodies such as circulating water, landscape water, and ballast water.

[0127] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a co-doped modified Ti4O7 electrode, characterized in that: The following steps are involved: Step 1: Mix Ti4O7 powder, metal source and non-metal source, and ball mill to obtain mixed powder; Step 2: Add a binder and an organic dispersant to the mixed powder, perform ultrasonic treatment, heat and stir, dry, and sinter to obtain a co-doped modified Ti4O7 electrode.

2. The method for preparing a co-doped modified Ti4O7 electrode according to claim 1, characterized in that: The amount of the metal source is 1-3wt% of the Ti4O7 powder, and the amount of the non-metal source is 5-9wt% of the Ti4O7 powder.

3. The method for preparing a co-doped modified Ti4O7 electrode according to claim 1, characterized in that: The metal source is one or more of ruthenium chloride, cobalt chloride or cobalt nitrate, cerium chloride, europium chloride or europium acetate, tin chloride and antimony chloride, and the non-metal source is one or more of boric acid, phosphoric acid, sodium fluoride and sodium sulfide.

4. The method for preparing a co-doped modified Ti4O7 electrode according to claim 1, characterized in that: The particle size of the Ti4O7 powder is 20-45 μm.

5. The method for preparing a co-doped modified Ti4O7 electrode according to claim 1, characterized in that: The amount of the binder used is 5-7wt% of the Ti4O7 powder.

6. The method for preparing a co-doped modified Ti4O7 electrode according to claim 7, characterized in that: The binder is nitrogen-containing heterocyclic zinc-based metal organic framework nanoparticles.

7. The method for preparing a co-doped modified Ti4O7 electrode according to claim 7, characterized in that: The organic dispersant is selected from one or more of isopropanol, ethanol and acetone.

8. The method for preparing a co-doped modified Ti4O7 electrode according to claim 1, characterized in that: The ball milling process is as follows: the rotation speed is 1100-1400 r / min, and the time is 20-30 min; The ultrasonic time is 30-50min, the heating and stirring temperature is 50-70°C, the stirring speed is 200-300r / min, the drying temperature is 70-90°C, and the drying time is 15-24h; The sintering process is as follows: sintering heating rate of 40-70°C / min, sintering temperature of 1100-1200°C, sintering time of 15-30min, and high pressure condition of 2-4MPa.

9. A co-doped modified Ti4O7 electrode, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. The use of a co-doped modified Ti4O7 electrode according to claim 9, characterized in that: Used for water treatment.

Citation Information

Patent Citations

  • Method of preparing electrode material by utilizing Ti4O7 powder

    CN103303971A

  • Circular tubular titanium black membrane electrode with electrochemical oxidation activity and preparation method of circular tubular titanium black membrane electrode

    CN105776429A

  • Surface-modified reactive electrochemical membrane and preparation method thereof

    CN108187507A

  • Ti<n>O<2n-1> doped electrode, and preparation method thereof and use thereof

    CN108911052A

  • Preparation method of rare earth metal doped Ti4O7 electrode

    CN113213594A

Cited By

  • Preparation method of electrode with phosphorus-doped induced Ti4O7 lattice strain and application of electrode in deep purification of electro-catalytic enhanced pharmaceutical wastewater

    CN120622622A

  • Preparation method of phosphorus-doped electrode inducing Ti4O7 lattice strain and application of the electrode in electrocatalytic reinforcement of advanced purification of medical wastewater

    CN120622622B